2020
DOI: 10.1039/c9tc05913j
|View full text |Cite
|
Sign up to set email alerts
|

A stretchable and compressible ion gel based on a deep eutectic solvent applied as a strain sensor and electrolyte for supercapacitors

Abstract: A deep eutectic solvent ion gel applied as a sensor for monitoring the grasping motion and as an electrolyte for symmetrically structured supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 86 publications
5
116
0
Order By: Relevance
“…Hong et al locked the conductive DES in a double network ion gel for supercapacitor. [100] The ion gel was produced by the free radical polymerization of acrylamide in a DES (composed of choline chloride, urea, and glycerol) and cellulose fiber mixture. Benefiting from the high ionic conductivity (0.58 mS cm −1 ) and a wide operating voltage window (2.0 V) of DES-based ion gel, the fabricated supercapacitors exhibited a high specific capacitance of 76.6 F g −1 at 1.0 A g −1 and a high energy density of 10.64 Wh kg −1 at a power density of 500 W kg −1 .…”
Section: Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al locked the conductive DES in a double network ion gel for supercapacitor. [100] The ion gel was produced by the free radical polymerization of acrylamide in a DES (composed of choline chloride, urea, and glycerol) and cellulose fiber mixture. Benefiting from the high ionic conductivity (0.58 mS cm −1 ) and a wide operating voltage window (2.0 V) of DES-based ion gel, the fabricated supercapacitors exhibited a high specific capacitance of 76.6 F g −1 at 1.0 A g −1 and a high energy density of 10.64 Wh kg −1 at a power density of 500 W kg −1 .…”
Section: Supercapacitorsmentioning
confidence: 99%
“…Different gels composed of a DES and polymer matrix were also prepared as quasi‐solid‐state electrolytes for supercapacitors. [ 99,100 ] An ecofriendly poly(vinyl alcohol)/Ace/LiClO 4 (PAL) DES‐based gel electrolyte with a high ionic conductivity of ≈12 mS cm −1 was developed by adding PVA into the LiClO 4 /Ace DES. It was used for high‐voltage wearable asymmetric supercapacitors (HVWASCs) with a large anodic voltage of 4.2 V. [ 99 ] The HVWASCs exhibited outstanding energy density and power capability (245 Wh kg −1 at 0.18 kW kg −1 and 98 Wh kg −1 at 95.3 kW kg −1 ).…”
Section: Dess For Energy Storage Applicationsmentioning
confidence: 99%
“…The value is much higher than that of PHEMA based‐DES gel electrolytes and is quite comparable to the recent reports on similar activated‐carbon electrodes studied in DES gel electrolyte. [ 24,26 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] Shu Hong et al reported the highly flexible PAM/cellulose supported DES (choline chloride/urea/glycerol)‐based gel which was applied as sensors to monitor human motion and also served as a solid‐state electrolyte in a supercapacitor with outstanding electrochemical performances. [ 26 ] Although the above reports have demonstrated the application of DES gels in nonvolatile devices applications, there is still a need to conduct more research toward stretchable DES gel electrolytes with high ionic conductivity and other functions (self‐healable and recoverable) for safe and efficient flexible devices. On one hand, the inverse relationship between mechanical strength and conductivity makes it challenging to develop stretchable DES gel electrolytes with high ionic conductivity comparable to that of liquid DES electrolyte in electrochemical device.…”
Section: Introductionmentioning
confidence: 99%
“…[99][100][101][102] Ionogels rarely have the leakage problem because of the reinforced capillary force. [103,104] One successful example was trapping a deep eutectic solvent of ChCl-EG in a gelatin network (22 wt%), which was robust against mechanical pressing (Figure 13e). [105] A capacitive sensor was fabricated by placing an insulator layer between two deep eutectic solvent gels (Figure 13f).…”
Section: General Formula Termsmentioning
confidence: 99%